Kesenian Jaranan dan Bantengan di Pemukiman Muslim Kabupaten Kediri - Nilla Alysia Anjayani (Qurthuba: The Journal of History and Islamic Civilization, 2020)
Abstract: This article discusses the traditional Jaranan and Bantengan arts in the Muslim community of Kediri. This research focuses on: 1) What is the background of the emergence of Jaranan and Bantengan in the area 2) What is the series of activities for Jaranan and Bantengan 3) What are the views of the scholars towards Jaranan and Bantengan. This arts research uses qualitative research methods as well as cognitive anthropological theory to understand the problems involved in the research. The data analysis technique used in the Jaranan and Bantengan arts research is a descriptive data analysis technique, where data is presented based on what is obtained from informants and written sources as is. The results of this study are that the relationship between humans and culture that exists in the Jaranan and Bantengan arts can be seen in the Jaranan and Bantengan art activities in the Muslim residential environment in Kuwik village. Not only that. However, Muslim leaders in the village of Kuwik also have different views on the art of jaranan and banteng. From the Muhammadiyah leadership, they consider this to be bid'ah, including shirk, while Nahdlatul Ulama figures believe that the arts are permissible as a form of tolerance, because whatever what is done while not causing harm in Islam is permissible. Keywords: art, culture, jaranan, bantengan